2017
DOI: 10.1515/jvetres-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Detection of avian reoviruses in wild birds in Poland

Abstract: IntroductionThe purpose of this study was to determine the occurrence of avian reovirus (ARV) infections in wild birds in Poland and attempt to propagate the selected ARV strains in chicken embryo kidney (CEK) cells or chicken SPF embryos.Material and MethodsThe study included 192 wild birds representing 32 species, collected between 2014 and 2016. A part of the S4 segment encoding the σNS protein of avian reoviruses (ARVs) isolated from different species of wild birds from that period was amplified.ResultsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Avian reovirus (ARV) infections of chickens are major causes of economic problems for commercial poultry producers throughout the world [2]. Economic losses caused by ARV infections in chickens are often the result of poor performances such as extenuated weight gains, high feed conversion ratio, decreased egg production, reduced marketability of affected birds, and also increased diseases susceptibility [3].…”
Section: Introductionmentioning
confidence: 99%
“…Avian reovirus (ARV) infections of chickens are major causes of economic problems for commercial poultry producers throughout the world [2]. Economic losses caused by ARV infections in chickens are often the result of poor performances such as extenuated weight gains, high feed conversion ratio, decreased egg production, reduced marketability of affected birds, and also increased diseases susceptibility [3].…”
Section: Introductionmentioning
confidence: 99%
“…In studies that reported high prevalence of ARV infection, specimens come from birds with clinical signs of infection, such as arthritis, tenosynovitis, enteric syndromes, in addition to more severe cases when central nervous system is compromised and death 24,55 . In USA, Lu et al 7 investigated ARV from tendons, synovial tissues and viscera from chickens, turkeys, partridges, quails and pheasants, that presented clinical signs, and all of 311 specimens analyzed on that study were positive for ARV.…”
Section: Discussionmentioning
confidence: 99%
“…The σC sequence is used as a genetic marker to characterize and classify ARV isolates into different six or seven genotypic clusters (8,9). The σNS protein encoded by the segment S4, has been reported for its single-stranded RNA (ssRNA) binding activity, and it is divided into diverse lineages that conserved by host origin of ARVs (10,11); as well it has been used for diagnostic analysis (10,12).…”
Section: Introductionmentioning
confidence: 99%